Smart and green solutions for transport systems : 16th Scientific and Technical Conference "Transport Systems. Theory and Practice 2019" selected papers /: 16th Scientific and Technical Conference "Transport Systems. Theory and Practice 2019" selected papers. (2020) - Unknown
No abstract available